DEVELOPING SELF-CONFIDENCE FOR STUDENTS WITH SPECIAL NEEDS BY IMPLEMENTING INTERPERSONAL COMMUNICATION - Dyva Claretta; Sumardjijati Sumardjijati; Yuli Candrasari (Jurnal Ilmu Komunikasi, 2020)
Students with special needs have the right to pursue an education as equal as the other regular students so they are able to develop their self potentials and socialize with common societies. Therefore, there are 25 inclusive schools (Non- SLB) spread around Surabaya since 2009, helping to break the education gaps for these students. Students with special needs are classified into those who are deaf or mentally disabled, have learning difficulties, slow learners, and down-syndromes. Students with above average IQ are put into considerations and becoming the main reason to be in acceptance of students with special needs in order to receive the equal education with the regular students. At SMP 29 Surabaya, there are currently 52 students with special needs studying in the 7th, 8th, and 9th grades in the hope of getting the equal subject materials with the ones that regular students have. In this case being the subject’s teacher, teachers are required to have certain pedagogical competency. Implementing pedagogical communication requires certain mastery of psychological and interpersonal communication for the students. Irwin Altman and Damas Taylor proposed a social penetration theory that is related to interpersonal relations and internal cognitive developments. The methodology of this study was conducted with descriptive-qualitative through in-depth interviews, both for regular teachers and competent teachers suited with classification of students with special needs. The results of the study found that there is a need for supervision by teachers who have certain competency of pedagogical communication of students with special needs, especially with the aim to help developing students' confidence and discover their potential, both through primary and secondary communication.